Mekanisasi Pertanian dan Pengembangan Usaha Pelayanan Jasa Alsintan (UPJA) - Herlina Tarigan (Forum penelitian Agro Ekonomi, 2018)
Agricultural Machinery Services Business (UPJA) is an institution based on the awareness of limited agricultural land, inadequate agricultural labor, fast planting time, and important agricultural modernization. UPJA is expected to overcome farming problems as well as being a factor of economic growth through capital accumulation and agricultural competitiveness. This paper is a critical review that aims to analyze agricultural mechanization and institutional development of UPJA as a rural economic institution for optimizing agricultural machinery. Results of the analysis show that the application of agricultural mechanization has been able to accelerate production process as well as to increase production and farming profits. The Special Effort (Upsus) program through agricultural machinery assistance has not run optimally. One way for optimizing the program is to grow and build UPJA as a manager of agricultural machinery. UPJA has the potential to spur the development of modern agriculture and at the same time it drives farmers’ economy in rural areas. Comprehensive and professional handling of UPJA is possible to develop this institution into a farmers’ corporation. AbstrakUsaha Pelayanan Jasa Alsintan (UPJA) adalah lembaga yang dibangun dari kesadaran bahwa lahan pertanian di Indonesia sudah relatif sempit, tenaga kerja pertanian makin terbatas, perlu mengejar waktu tanam, dan pentingnya modernisasi pertanian. UPJA diperkirakan mampu mengatasi masalah usaha tani sekaligus menjadi faktor pertumbuhan ekonomi melalui akumulasi modal dan daya saing pertanian. Tulisan ini merupakan review ilmiah (critical review) yang bertujuan menganalisis mekanisasi pertanian dan  pengembangan kelembagaan UPJA sebagai lembaga ekonomi desa dalam rangka optimalisasi alsintan. Hasil analisis menunjukkan penerapan mekanisasi pertanian telah mampu mempercepat proses produksi, meningkatkan produksi, dan keuntungan usaha tani.  Program Upsus melalui bantuan alsintan belum berjalan secara optimal.  Salah satu bentuk upaya optimalisasi adalah dengan menumbuhkan dan membangun UPJA sebagai pengelola alsintan. UPJA potensial memacu berkembangnya pertanian modern sekaligus menggerakkan ekonomi petani di pedesaan.  Penanganan UPJA secara menyeluruh dan profesional berpotensi mengembangkan lembaga ini menjadi korporasi petani.